Representation of Disobedient Children and Replies in Archipelago Folklore: A Comparative Study of Simaranda and Si Lancang - Atika Zikri; Hasanuddin WS (CV. Syntax Corporation Indonesia, 2025)
This study analyzes the representation of disobedience and retaliation in two archipelago folklore, Simaranda (Batak Toba) and Si Lancang (Riau Malay), through a qualitative-descriptive-comparative approach. The analysis focuses on forms of disobedience, counter-responses, narrative structures, and underlying cultural values using Vladimir Propp's structuralism theory and LÃ©vi-Strauss anthropology. The results of the study show that Simaranda describes disobedience as a rejection of family ties in the patrilineal social system, while Si Lancang displays disobedience as arrogance due to prosperity and denial of origin. The retribution in Simaranda is manifested through a curse that turns the perpetrator into stone, while in Si Lancang through a natural disaster that sinks the ship. Both stories reflect moral justice and the balance of the cosmos according to the worldview of the society. Thus, folklore not only serves as a means of moral education, but also as a social mechanism to maintain family and cultural values in the midst of changing times.